Piezo1 activation induces relaxation of the pudendal artery and corpus cavernosum - Dela Justina, Vanessa; de Freitas, Raiany Alves; Arishe, Olufunke O.; Giachini, Fernanda R.; Webb, R. Clinton; Priviero, Fernanda (Frontiers in Physiology, 2023)
Piezo1 channel is a sensor for shear-stress in the vasculature. Piezo1 activation induces vasodilation, and its deficiency contributes to vascular disorders, such as hypertension. In this study, we aimed to determine whether Piezo1 channel has a functional role in the dilation of pudendal arteries and corpus cavernosum (CC). For this, male Wistar rats were used, and the relaxation of the pudendal artery and CC was obtained using the Piezo1 activator, Yoda1, in the presence and absence of Dooku (Yoda1 antagonist), GsMTx4 (non-selective mechanosensory channel inhibitor) and L-NAME (nitric oxide synthase inhibitor). In the CC, Yoda1 was also tested in the presence of indomethacin (non-selective COX inhibitor) and tetraethylammonium (TEA, non-selective potassium channel inhibitor). The expression of Piezo1 was confirmed by Western blotting. Our data show that Piezo1 activation leads to the relaxation of the pudendal artery and CC as the chemical activator of Piezo1, Yoda1, relaxed the pudendal artery (47%) and CC (41%). This response was impaired by L-NAME and abolished by Dooku and GsMTx4 in the pudendal artery only. Indomethacin and TEA did not affect the relaxation induced by Yoda1 in the CC. Limited tools to explore this channel prevent further investigation of its underlying mechanisms of action. In conclusion, our data demonstrate that Piezo1 is expressed and induced the relaxation of the pudendal artery and CC. Further studies are necessary to determine its role in penile erection and if erectile dysfunction is associated with Piezo1 deficiency.